Biological of black bug Paraeuscosmetus pallicornis (Hemiptera: Lygaeidae) on two varieties of rice plants at laboratory - Nurhabibah; Tobing, Cyccu; Hasanuddin (Jurnal Online Pertanian Tropik, 2019)
The objective of the research was to study the biology of black bug Paraecosmitus palicornis insects on two varieties of rice at laboratory. The research was conducted at Plant Pest Laboratory of Agricultural Faculty University of Sumatera Utara, Medan from September to December 2017. The research used by descriptive method and complete randomized design with nine replications. The results showed that total life cycle on Mekongga varieties was ±27.1 days and a female laids ±41.56 eggs. Total life cycle on Mapan 05 varieties was ±26.2 days and female laids ± 12,55 eggs.